Cross-cultural comparison of the relationships among perceived risk online, perceived usability and satisfaction during browsing of a tourist website - Juan Miguel Alcántara-Pilar; Salvador Del Barrio-García; Esmeralda Crespo-Almendros (Tourism & Management Studies)
The purpose of this paper is to empirically analyze the influence of culture on the relationships among perceived risk, perceived usability and satisfaction online, in two cultures: Spain (high uncertainty avoidance and low individualism) and the United Kingdom (low uncertainty avoidance and high individualism). The sample comprised 314 Internet users, 119 of whom were Spanish and 195 British. They were asked to browse the experimental website of a fictitious tourist destination. The findings indicated that there are significant differences between the direct influence of perceived risk on perceived usability and also the indirect relationship between perceived risk and satisfaction online during browsing of the tourist website, and that these differences are moderated by the uncertainty avoidance dimension.